Harmful association of sprinting with muscle injury occurrence in professional soccer match-play: A two-season, league wide exploratory investigation from the Qatar Stars League - Gregson, W.; Di Salvo, V.; Varley, M. C.; Modonutti, M.; Belli, A.; Chamari, K.; Weston, M.; Lolli, L.; Eirale, C. (Journal of Science and Medicine in Sport, 2020)
Objectives: To investigate the impact of physical efforts performed in the period preceding activity as a potential risk factor of muscle injury during match-play within a sample of professional soccer players. Design: Observational cohort study. Methods: Match load (running [>14.4-19.8 km/h], high-speed running [>19.8-25.2 km/h], sprinting [>25.2 km/h], leading and explosive sprint type) averaged in 1-min and 5-min periods prior to an event or non event for 29 professional outfield soccer players. Conditional logistic and Poisson regression models estimated the relationship between load and injury for a 2 within-subject standard deviation in match load or 1-action increment in the number of sprinting activities, respectively. Associations were deemed beneficial or harmful based on non-overlap of the 95% confidence intervals against thresholds of 0.90 and 1.11, respectively. Results: An increment in sprinting distance [+2-SDs = 11 m] covered over a 1-min period (odds ratio [OR]: 1.22, 95%CI, 1.12 to 1.33) increased the odds of muscle injury. Conclusions: Our study provides novel exploratory evidence that the volume of sprinting during competitive soccer match-play has a harmful association with muscle injury occurrence.